Hide and don't seek ebook And other very scary stories. - Rissi, Anica Mrose (2021)
A contemporary collection of original short stories by Anica Mrose Rissi that is sure to elicit chills, laughs, and screams, even from the most devoted fans of Scary Stories to Tell in the Dark! A game of hide-and-seek goes on far too long... A look-alike doll makes itself right at home... A school talent-show act leaves the audience aghast... And a summer at camp takes a turn for the braaaains... This collection of all-new spooky stories is sure to keep readers up past their bedtimes, looking over their shoulders to see what goes bump in the night. So if you're feeling brave, turn the page.